Tropical fossil mitogenomes: Holocene biogeography of two codistributed rodent genera from the Yucatán peninsula. (August 2021) - Gutiérrez-García, Tania A.; Shaney, Kyle J.; Vázquez-Domínguez, Ella; Enk, Jacob; Arroyo-Cabrales, Joaquín
Graphical abstract: Highlights: We used fossils from stratigraphic strata (2, 000–12, 000 years old) from Loltún cave, Yucatán, Mexico. We successfully reconstructed partial ancient mitogenomes from tiny rodent fossil hemimandibles. Our results provide evidence for biogeographic processes that affected Yucatán species during the Holocene. The region was dominated by a wet and cold climate during the LGM that recently changed to warmer and much dryer. Our results support the potential for phylogenomic research from fossils recovered from tropical caves. Abstract: Integrating ancient fossil DNA with modern genetic samples is aiding in advancing the fields of ecology and biogeography. However, wide gaps in the fossil record still remain throughout the tropics, while genetic and genomic datasets from tiny (<50 mg) ancient tropical fossils recovered from small mass species (<100 g) are particularly scarce. We studied tropical fossil hemimandible samples of two rodent genera from seven stratigraphic strata from Loltún cave, Yucatán, Mexico, dated 2, 000–12, 000 years ago. We also selected contemporary museum skin samples of these rodents and amplified mitochondrial DNA from both sources (fossil and museum) with next generation sequencing. We recovered the first nearly complete contemporary and partial fossil mitogenomes for Ototylomys and Oryzomys . Ancient and contemporary samples of both species clustered together, whilst exhibiting a topology in which haplotypes differentiated in correspondence with biogeographic breaks. Accordingly, Ototylomys and Oryzomys distinct lineages are associated with biogeographic provinces and breaks across neotropical Mexico and Central America. Results from Loltún provide further evidence for biogeographic processes that affected Yucatán species during the Holocene. Relative abundances of the studied genera's fossil remains differed among the stratigraphic layers, mirroring the expansion and contraction of their populations in response to changing climatic conditions and shifting plant regimes. Oryzomys fossil remains are much less abundant at the most recent and oldest layers, supporting a biogoegraphic hypothesis where this region was dominated by a wet and cold climate during the Last Glacial Maximum and which, only a few thousand years ago, changed to a warmer and much dryer climate.